Reciprocal Activating Interaction between Natural Killer Cells and Dendritic Cells - Gerosa, Franca (The Rockefeller University Press, 2002)
We analyzed the interaction between human peripheral blood natural killer (NK) cells and monocyte-derived immature dendritic cells (DC). Fresh NK cells were activated, as indicated by the induced expression of the CD69 antigen, and their cytolytic activity was strongly augmented by contact with lipopolysaccharide (LPS)-treated mature DC, or with immature DC in the presence of the maturation stimuli LPS, Mycobacterium tuberculosis or interferon (IFN)-α. Reciprocally, fresh NK cells cultured with immature DC in the presence of the maturation stimuli strongly enhanced DC maturation and interleukin (IL)-12 production. IL-2–activated NK cells directly induced maturation of DC and enhanced their ability to stimulate allogeneic naive CD4+ T cells. The effects of NK cells were cell contact dependent, although the secretion of IFN-γ and TNF also contributed to DC maturation. Within peripheral blood lymphocytes the reciprocal activating interaction with DC was restricted to NK cells, because the other lymphocyte subsets were neither induced to express CD69, nor induced to mature in contact with DC. These data demonstrated for the first time a bidirectional cross talk between NK cells and DC, in which NK cells activated by IL-2 or by mature DC induce DC maturation.